A Review: Application of Bromelain Enzymes in Animal Food Products - Ririn Fatma Nanda; Rini Bahar; Daimon Syukri; Nguyen Ngoc Anh Thu; Anwar Kasim (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2020)
This review focuses on the use of bromelain in various applications in animal products with the latest literature so that it can provide information on what parts of this enzyme can be applied. Bromelain is a protease enzyme found in stems (EC 3.4.22.32), leaves, crowns, fruit skins, fruit flesh (EC 3.4.22.33) and fruit tubers in pineapple. Bromelain has been exploited commercially in many applications in the food industry (baking industry), drinks industry (stabilizers in beer), tenders (meat), and pharmaceuticals (anti-tumorigenic agents). However, not all types of proteins can be hydrolyzed by bromelain, such as keratin which can only be hydrolyzed by keratinase, this is because the enzymes work specifically. In animal food products, bromelain is applied as a meat tenderizer, making of protein hydrolyzate products, cheese and also fish sauce product. The application of bromelain to animal food products has proven that hydrolyzed products using this enzyme can increase umami taste, which means that bromelain has great potential when applied to animal food products. Bromelain is useful in the processing of some animal food products because bromelain works specifically and is very active in animal protein such as milk, meat and collagen.